NI LabVIEW based camera system used for gait detection - Salánki, D; Sarvajcz, K (IOP conference series. Materials Science and Engineering, 2019)
In these times, with the development of the world, biometric identification systems are becoming more and more widespread. Access control systems, but even the most mid-range smartphones have biometric authentication features, and even ID cards can include a person's fingerprint. The research group previously realized a rudimentary gait recognition system, which was upgraded to a multicamera system with high-resolution cameras and instead of reference points, the new version recognizes different templates. The program can compare and evaluate the functions that are matched to the reference curve and the current curve in a specific way, whether two walking images are identical. The comparison is decided by the definite integrals of the two suited functions. The self-developed gait recognition system was tested by the research team on several test subjects and according to the results, permission was never given to a strange person.